Three-year efficacy and safety of new- versus early-generation drug-eluting stents for unprotected left main coronary artery disease insights from the ISAR-LEFT MAIN and ISAR-LEFT MAIN 2 trials - Cassese, Salvatore; Kufner, Sebastian; Xhepa, Erion; Byrne, Robert A.; Kreutzer, Johanna; Ibrahim, Tareq; Tiroch, Klaus; Valgimigli, Marco; Toelg, Ralph; Fusaro, Massimiliano; Schunkert, Heribert; Laugwitz, Karl-Ludwig; et al. (Clinical Research in Cardiology, 2016)
Background: In percutaneous coronary intervention (PCI) patients new-generation drug-eluting stent (DES) has reduced adverse events in comparison to early-generation DES. The aim of the current study was to investigate the long-term clinical efficacy and safety of new-generation DES versus early-generation DES for PCI of unprotected left main coronary artery (uLMCA) disease. Methods: The patient-level data from the ISAR-LEFT MAIN and ISAR-LEFT MAIN 2 randomized trials were pooled. The clinical outcomes of PCI patients assigned to new-generation DES (everolimus- or zotarolimus-eluting stent) versus early-generation DES (paclitaxel- or sirolimus-eluting stent) were studied. The primary endpoint was the composite of death, myocardial infarction (MI), target lesion revascularization and stroke (MACCE, major adverse cardiac and cerebrovascular event). Results: In total, 1257 patients were available. At 3 years, the risk of MACCE was comparable between patients assigned to new-generation DES or early-generation DES (28.2 versus 27.5 %, hazard ratio—HR 1.03, 95 % confidence intervals—CI 0.83–1.26; P = 0.86). Definite/probable stent thrombosis was low and comparable between new-generation DES and early-generation DES (0.8 versus 1.6 %, HR 0.52, 95 % CI 0.18–1.57; P = 0.25); in patients treated with new-generation DES no cases occurred beyond 30 days. Diabetes increased the risk of MACCE in patients treated with new-generation DES but not with early-generation DES (Pinteraction = 0.004). Conclusions: At 3-year follow-up, a PCI with new-generation DES for uLMCA disease shows comparable efficacy to early-generation DES. Rates of stent thrombosis were low in both groups. Diabetes significantly impacts the risk of MACCE at 3 years in patients treated with new-generation DES for uLMCA disease. ClinicalTrials.gov Identifiers: NCT00133237; NCT00598637.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Drug-eluting stent; Everolimus; Left main coronary artery; Paclitaxel; Percutaneous coronary intervention; Sirolimus; Zotarolimus